The Coping Strategies in Biographies of Polish Middle- Class Representatives of (Post)Transformation Period - Burski, Jacek (Qualitative Sociology Review, 2019)
The article focuses on the problem of life strategies adapted by the representatives of young Polish middle-class in the (post)transformation period in Poland towards different aspects of social change. On the basis of two research projects focused on the consequences of the Polish systemic transformation, I discuss issues related to biographical experiences of this process. The main theoretical and methodological background is concentrated on using the autobiographical narrative interview to analyze coping strategies in relation to the class position of examined cases. The interviews taken under consideration have been conducted with young men who could be described as middle-class members.